Child Care Arrangements and Labor Supply - Daniela Del Boca (Inter-American Development Bank (IDB), 2015)
This paper discusses several approaches to examining the relationship between child care and mothers' labor supply. The focus is on child care for children aged 0-3, because this is a critical period for working mothers and their children and because most European and American households with children aged 3-5 already use child care centers. The paper provides data concerning availability of, government spending on, and quantity and quality standards for child care in different countries, then compares different approaches to the determinants of child care demand and labor supply. The paper subsequently reviews and compares empirical results regarding the impact of child care costs, availability and quality. Finally, the paper discusses different impacts across different groups and provides concluding remarks.
hdl:11319/6812
Keywords: J13; I2; H75; 330; Child care; Mothers'employment; Child development